An Adenosine Triphosphate- Dependent 5′-3′ DNA Helicase From sk1-Like Lactococcus lactis F13 Phage - Chmielewska-Jeznach, Magdalena; Steczkiewicz, Kamil; Kobyłecki, Kamil; Bardowski, Jacek K.; Szczepankowska, Agnieszka K. (Frontiers in Microbiology, 2022)
Here, we describe functional characterization of the early gene (gp46) product of a virulent Lactococcus lactis sk1-like phage, vB_Llc_bIBBF13 (abbr. F13). The GP46F13 protein carries a catalytically active RecA-like domain belonging to the P-loop NTPase superfamily. It also retains features characteristic for ATPases forming oligomers. In order to elucidate its detailed molecular function, we cloned and overexpressed the gp46 gene in E. coli. Purified GP46F13 protein binds to DNA and exhibits DNA unwinding activity on branched substrates in the presence of ATP. SEC-MALS experiments demonstrate that GP46F13 forms oligomers, and further pull-down assays show that GP46F13 interacts with host proteins involved in replication (i.e., DnaK, DnaJ, topoisomerase I and single-strand binding protein). Taking together the localization of the gene and the obtained results, GP46F13 is the first protein encoded in the early-expressed gene region with helicase activity that has been identified among lytic L. lactis phages up to date.